Parents Contribution in Fine Motor Skills of Children with Intellectual Disability - Ernisa Purwandari; Atien Nur Chamidah; Suparno Suparno (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
The fine motor skills of children with intellectual disabilities vary and are influenced by several factors including parents’ contributions. This study was set to determine the children's motor skills and the role of parents in the fine motor skills of children with intellectual disabilities. The subjects of this study were 47 children with intellectual disabilities aged 7-8 years and their parents. Fine motor skills are obtained through assessment using fine motor skills instruments of children with intellectual disabilities. Meanwhile, the data on the role of parents on children's fine motor skills were gathered through a questionnaire. The results showed that the fine motor skills of this group mostly developed as expected. The contribution of parents to the children's motor skills is shown by providing early stimulation and early intervention through involving children in various activities in daily life.